The The Role of Agencies and Strategy Innovation on Regular Customers at PT. XZY Branch of Ben Line Shipping - Kwartama, Agung; Samiyono; Orgunsanya, Victoria Abosede (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: PT. XYZ faces challenges in ensuring customer and crew satisfaction, as well as inaccuracies in logging ship arrivals and departures, leading to increased waiting costs. As a representative of Ben Line Agencies, PT. XYZ acknowledges the maritime industry's potential and is dedicated to fostering robust cooperation to promote national sector growth.Purpose: The findings indicate that both agency services and business strategy have positive results for customer loyalty at PT. XYZ Ben Line Agencies Indonesia Representative.Design/Methodology/Approach: The research makes a method with quantitative analysis, using main data through questionnaires delivered to 77 customer respondents who are agents of PT. XYZ, specifically at the Jakarta branch of Ben Line shipping. The findings indicate a positive result of agency services on customer satisfaction at PT. XYZ, as well as a notable positive effect of business strategy on customer satisfaction. Furthermore, both factors together significantly influence customer satisfaction at PT. XYZ Ben Line Agencies Indonesia.Findings/Result: The agency services at PT. XYZ, representing Ben Line Agencies Indonesia, have a notable and substantial impact on customer loyalty. This implies that effective agency services are likely to make sure loyalty significantly. Understanding this influence is crucial for assessing the service reach in fulfilling user requirements.Conclusion: We recommend that PT XYZ concentrate on enhancing the response speed of the support team or customer service. This could involve improving communication processes, providing further training for the support team, or implementing systems that accelerate responses to customer needs.Originality/Value (State of the Art): A strong and significant impact of business strategy on customer satisfaction has been observed at PT. XYZ, a representative of Ben Line Agencies Indonesia. This relationship is crucial for assessing business success. An effective business strategy encompasses several factors, including competitive pricing, relevant product or service development, and efficient supply chain management. Keywords: role of agency, bussiness inovation, customer royalty and statisfaction, business strategy, strategy innovation